Current Microbial Isolates and Their Antimicrobial Susceptibility Pattern from Wound Infection in a Tertiary Care Hospital - Begum, Taslima; Nahar, Azizun; Siddique, Prothoma Rahman; Numan, Farzana; Sarwar, Taslima; Islam, Hiba; Rahman, AFM Shahidur (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Wound infection is one of the leading cause of mortality and morbidity worldwide. Objectives: To identify the current microbial isolates and their antimicrobial susceptibility pattern from wound infection in a tertiary care hospital in Dhaka city. Materials & Methods: This retrospective study was conducted in the department of Microbiology at Holy Family Red Crescent Medical College Hospital, Dhaka from July 2019 to December 2020 for a period of one and half years. Written consent was taken from corresponding authority. Microsoft Excel software was used for data analysis. A total 134 wound swab / pus were collected from the patients who were visited in outpatient department and were admitted at inpatient department with suspected wound infection. All samples were processed aerobically on Blood agar, MacConkeys agar media and incubated at 370C for 24 hours. Organisms were identified by standard procedures including colony characters, Gram staining and biochemical reactions. Antimicrobial susceptibility testing of all the isolates were performed by Kirby Bauer’s disc diffusion method. Results: A total 134 samples were analyzed. Of them, predominant populations were male 76(56.72%) and remaining were female 58(43.28%). Out of 134 samples 102 (76.11%) was culture positive. Culture positive was observed higher in inpatient department (IPD) 80 (78.43%) than outpatient department (OPD) 22 (21.57%). Majority of isolates were Gram negative bacteria. Among them predominant bacteria was E. coli 26(25.49%) followed by Klebsiella spp. 24(23.53%), Pseudomonas spp. 15(14.71%) & Proteus spp. 04(3.92%). Among the Gram - positive isolates 30(29.41%) was Staph. aureus. E. coli showed higher sensitivity to meropenem 88.46% & gentamicin 80.76%. Other drugs showed sensitivity to amikacin 65.38%, amoxicillin/clavulenic acid 53.84%, tetracycline 46.15%, ceftriaxone & ceftazidime 42.30%, trimethoprime/ sulfamethoxazole 34.61% & cefuroxime 23.07%. In Klebsiella spp. meropenem showed higher sensitivity 79.16% & gentamycin 66.66%. Other drugs like amikacin showed 58.33%, trimethoprime/ sulfamethoxazole 45.83%, ceftazidime & ciprofloxacin 20.83% sensitivity. Low sensitivity 16.66% to amoxicillin/clavulanic acid, cefuroxime, ceftriaxone, & tetracycline was found. Proteus spp. showed 75% sensitivity to meropenem. Cefuroxime, ceftriaxone, ciprofloxacin, ceftazidime, gentamycin, amikacin, trimethoprime/ sulfamethoxazole showed very low sensitivity 25% & amoxycillin/clavulanic acid showed 100% resistance. Pseudomonas spp. showed highest sensitivity 83.33% to piperacillin tazobactum, amikacin & imipenem, 77.77% to meropenem, 66.66% to gentamycin, 61.11% to ciprofloxacin, 50% to ceftazidime & 33.33% to cefepime. All the isolate of Staph. aureus was sensitive to amikacin 90%, amoxyclav 80%, cloxacillin 70%, ciprofloxacin 70%, gentamicin 63.33% & azythromycin showed lower sensitivity 43.33%. Conclusion: Most of the injectable antibiotics showed higher sensitivity which is an alarming sign for the clinician to treat wound infection. Periodic review of the bacteriological profile and antibiotic sensitivity pattern is highly essential. Antibiotic policy & infection control program should be included in every hospital to reduce this drug resistance. J Shaheed Suhrawardy Med Coll 2021; 13(1): 80-85